Exploring Adolescent Stress and Coping Strategies in School: A Qualitative Study of Upper Secondary School Students in Norway - Ingvild Røsand; Anne Torhild Klomstén (Nordisk tidsskrift for utdanning og praksis)
In Norway, the interdisciplinary topic health and life skills has been mandated in the national K-12 curriculum since 2020, with the intention of promoting students’ physical and mental health and enhancing their social and academic coping resources. This paper aims to illuminate students’ perspectives on stress and coping strategies in Norwegian schools, within the framework of health and life skills education. The data is derived from a case study design with semi-structured interviews with 26 Norwegian upper secondary school students. The results identify three main coping strategies used by students when facing school stress: (1) avoidance, (2) substitution, and (3) problem-solving. Although the results identify varied coping strategies used by upper secondary students facing school stress, none of the study participants described coping based on situational specifics (coping flexibility). Our findings also identified that participants talk only about distress (never eustress), and that furthermore, they connect distress mainly with school. These findings highlight the critical importance of teaching about stress and coping strategies in health and life skills education.